Pelatihan Gaya Kepemimpinan Dalam Peningkatan Motivasi Entrepreneurship pada Organisasi PKK Desa Pangrango, Kecamatan Kadudampit, Kabupaten Sukabumi - Rosmiati, Neni; Almardiah, Gina (Indra Institute Research & Publication, 2023)
Leadership style training plays a significant role in enhancing the motivation of entrepreneurial spirits. This activity aims to boost the entrepreneurial drive among members of the Pangrango Village Family Welfare Movement (PKK) in the Kadudampit Subdistrict, Sukabumi Regency. The focus is on developing effective leadership styles. The training seminar involved a total of 29 participants and was conducted through offline brainstorming sessions, enabling participants to interact directly and profoundly. Brainstorming sessions provided a platform for participants to share their perspectives, experiences, and thoughts on entrepreneurship and leadership. This approach facilitated open and collaborative discussions, thereby enhancing the understanding of challenges and opportunities in entrepreneurial development. The outcome of this training was an increased entrepreneurial motivation among the seminar participants. With a better grasp of effective leadership styles, participants are expected to apply these concepts in their efforts to develop and manage their own businesses. Furthermore, this training can also foster a spirit of collaboration and innovation, which are key factors in entrepreneurial success.